Analisis Pengaruh Harga dan Promosi Terhadap Tingkat Penjualan Pizza Hut di era Covid-19 - Juliana Juliana; Amelda Pramezwary; Catherine Catherine; Hermawan Dwitama; Indah Sentia (Cakrawala - Jurnal Humaniora, 2021)
Abstract-  This study aims to analyze the effect of price and promotion on the sales level of Pizza Hut in the Covid-19 era. This research is a basic research to fill the research gap in sales level studies. two hypotheses and tested using data collected from 150 respondents of pizza hut customers. This research is driven by the Covid-19 pandemic which has brought a downturn for companies in marketing products produced by these companies, especially companies in the field of food and beverage. Researchers use quantitative research with multiple linear regression analysis techniques to analyze how much influence the independent variables interact with. dependent variable. Researchers found that the variable that had the most significant influence on Pizza Hut sales in the Covid-19 era was promotion. The decline in Pizza Hut prices did have an effect on the increase in Pizza Hut sales but the effect was not too significant. This is due to the intense price competition to attract consumers' attention in this pandemic. Thus, it is evident that the Pizza Hut promotion strategy by attracting public sympathy can increase sales in the Covid-19 era.Keywords: price, promotion, sales level, covid-19